HOW GLOBAL FASHION IS TRANSFORMING THE PERCEPTION OF BEAUTY: THE NEW AESTHETICS INDUSTRY - Kotyk, Iryna (European Journal of Interdisciplinary Issues, 2025)
The relevance of the study is due to the growing influence of global aesthetic standards on the cultural and social processes of modern society. The aim of the article is to identify the mechanisms of formation and dissemination of modern ideas about beauty in the context of globalization of the fashion industry. The research methodology is based on the application of systemic and structural-functional approaches, which allowed for a comprehensive analysis of socio-cultural factors, media mechanisms and digital technologies that influence the transformation of aesthetic norms. It was found that the formation of global aesthetic standards is a consequence of the interaction of cultural globalization, the development of mass culture, urbanization processes and digital mediation, which together contributed to fashion going beyond local traditions and its transformation into a universal regulator of aesthetic guidelines. It was found that the dissemination of aesthetic norms is carried out through a complex system of mechanisms – from traditional media to social platforms, commercial strategies of brands and technologies of augmented and virtual reality, which act in concert and form stable visual patterns. Deep changes in the perception of beauty have been identified, associated with the combination of unified global ideals and inclusive trends, which leads to the emergence of new hybrid models of corporeality, expands the boundaries of representation and contributes to the rethinking of the norms of naturalness and “visual authenticity”. The study made it possible to trace the social, psychological, cultural and economic consequences of the spread of global aesthetic models: from increasing aesthetic pressure and the formation of dependence on media representations to the emergence of new forms of social stratification and the strengthening of the global economy of beauty. As a result, a holistic view of the modern fashion industry as a multi-level socio-cultural institution capable of simultaneously unifying and diversifying aesthetic norms has been formed. The practical significance of the results obtained lies in the possibility of using them for further cultural, sociological, media and interdisciplinary research, as well as for developing strategies for responsible communication, inclusive branding and balanced presentation of beauty standards in the fashion, educational and digital spheres.